The moderating effect of fuel prices on the market value of fuel efficiency, driving intensity, and CO₂ emissions - Daniel Klapper; Vlada Pleshcheva (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
In the current paper, we quantify the effect that fuel prices have on vehicle prices' responsiveness to fuel economy. We apply a hedonic price model to the German automobile market by using data on detailed technical specifications of high-sales vehicles of three sequential model years. In the contribution to previous research, our specification enables us to distinguish between consumers' valuation of fuel economy versus their reaction to changes in fuel prices. Two sources of changes in consumers' willingness-to-pay for better fuel economy are discussed - changes in the budget for driving a car and changes in capital investments in better car quality. We also discuss the subsequent changes in the optimal driving intensity and the resulting carbon dioxide emissions. Differences in the effects are studied for various car makes of both diesel and gasoline engines.
Keywords: D12; L62; Q41; Q51; 330; CO2 emissions; fuel economy; fuel prices; hedonic regression